EFFICACY AND SAFETY OF RETROGRADE INTRARENAL SURGERY (RIRS) FOR RENAL STONE CLEARANCE: A PROSPECTIVE INTERVENTIONAL STUDY. - Ranjan, Nikhil; Dheeraj, Kumar; Kumar, Rakesh; Babelay, Gaurav (Student's Journal of Health Research Africa, 2024)
Background The management of kidney stones has advanced with the development of minimally invasive techniques like Retrograde Intrarenal Surgery (RIRS). RIRS, which employs flexible ureterorenoscopy and laser lithotripsy, is a highly promising and safe method for the removal of stones, even in complicated cases. Recent technological improvements have expanded its use, particularly for larger stones (> 2 cm), which were previously treated through percutaneous nephrolithotomy. Aims This study seeks to assess the safety and efficacy of RIRS for renal stone clearance in adults. Key objectives include evaluating the success rate of stone removal and analyzing perioperative factors such as surgical duration, complications, and recovery. Methods Conducted at IGIMS, Patna, this interventional investigation was performed on 20 adult patients with kidney stones over one year. The surgery utilized a Holmium laser for stone fragmentation, with post-procedural evaluation through X-ray imaging. Data on stone clearance rates, procedure time, complications, and recovery were collated to examine the procedure’s safety as well as effectiveness. Results The study included 20 patients with a greater proportion of males and a mean age of 33.4 ± 10.6 years. The stones were mainly located in the middle calyx (40%) and lower calyx (20%), with an average size of 1.06 ± 0.36 cm. RIRS achieved a 100% stone-free rate, with an average surgical duration of 90 ± 18.7 minutes and an average duration of hospitalization (approx. 4.6 days). Complications were minimal, with 90% classified as Grade I and 10% as Grade II. A second RIRS session was required in 10% of cases, and 20% of patients needed a postoperative blood transfusion. Conclusion RIRS proved to be a promising treatment for renal stones, demonstrating high stone clearance rates with minimal complications. This technique offers a dependable alternative to traditional treatments, providing shorter hospital stays and manageable recovery outcomes.